Examining future-oriented discourse within reflective narratives as professional identity development for student teachers. Issue 3 (27th May 2021) - Muchnik-Rozanov, Yulia; Tsybulsky, Dina
ABSTRACT: Despite a growing awareness of the importance of future-oriented reflective practices among teacher-education researchers, there is a gap in the literature regarding the question of whether and in what way these kinds of written reflections promote the development of student teachers' professional identity. To fill this gap, the current study aims to explore the contribution of future-oriented discourse within written reflective narratives to the shaping of student teachers' professional identity. The participants of the study were 16 student teachers in their first year of studies towards a B.Ed. degree with a specialisation in science education. The data were obtained from the student teachers' reflective reports ( n = 32) submitted at the end of both the first and the second semesters. The data were analysed combining linguistic and content analyses. The main finding of the current study is that this kind of reflective practice contributes to the development of student teachers' professional identity in three main ways: It allows them to (1) predict the kind of teachers they are going to be, (2) formulate expectations of themselves as teachers, and (3) express concerns regarding their future as teachers.